Peraturan Perpajakan PP Nomor 23 Tahun 2018 sebagai Suntikan Hormon bagi Pelaku UMKM (?) - Ismayantika Dyah Puspasari; Zulistiani, Zulistiani (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
The purpose of this study is to analyze the positive impact of the issuance of Government Regulation no. 23 of 2018 on the growth of MSMEs in terms of capital, profits, and business value. The research method uses a qualitative phenomenological Tran-sendental approach to the concept of